Starch-based adhesive as well as preparation method and application thereof

The Pickering emulsion system is constructed through water-soluble colloids and liquid oils, and the water absorption and chemical reagent residues of traditional starch adhesives in high humidity environments are solved, and efficient moisture-proof and stable bonding performance is achieved, the production process is simplified and the production process is reduced. cost.

CN119193036APending Publication Date: 2024-12-27NINGBO INST OF TECH ZHEJIANG UNIV ZHEJIANG
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411299968.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Traditional starch-based adhesives are prone to absorb water and swelling in high humidity environments, and the use of chemical modification reagents leads to unstable adhesive performance, unsatisfactory moisture-proofing effect, and high production costs, so the environmental protection needs to be improved.

Method used

Water-soluble colloids and liquid oils are used to jointly build a stable Pickering emulsion system to form a high-efficiency starch adhesive, avoid the use of sodium hydroxide or other chemical reagents, and convert it into a hydrophobic gel through complex spatial molecules to improve moisture-proof performance.

Benefits of technology

It achieves moisture-proof effect with high-efficiency starch content and no chemical reagent residues, improves bonding performance and stability, simplifies production processes, reduces production costs, and improves environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005047338620000081
    Figure BDA0005047338620000081
Patent Text Reader

Abstract

The invention provides a starch-based adhesive as well as a preparation method and application thereof, and relates to the technical field of adhesives. The starch-based adhesive comprises the following components in parts by weight: 100 parts of water, 0.1-1 part of water-soluble colloid, 25-35 parts of natural starch and 2-5 parts of liquid grease. The preparation method comprises the following steps: S1, adding water-soluble colloid into water, and after the water-soluble colloid is fully dissolved, adjusting the pH value to 5-7 to obtain a colloidal solution; s2, adding natural starch into the colloidal solution obtained in the step S1, and shearing and emulsifying to form starch dispersion liquid; s3, adding liquid grease into the starch dispersion liquid obtained in the step S2, shearing and emulsifying to obtain Pickering emulsion, namely the starch adhesive capable of being industrially used. The obtained starch-based adhesive is high in effective starch content, stable in performance, safe, environmentally friendly, free of sodium hydroxide residues and capable of effectively preventing moisture after being glued.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesives, and in particular relates to a starch-based adhesive and a preparation method and application thereof. Background Art

[0002] Starch is a cheap, easily degradable, environmentally friendly, pure natural renewable resource. It is environmentally friendly when used to prepare adhesives. It has a simple production process, small equipment investment, low production cost, and a wide range of sources and uses. It has been widely used in the bonding of corrugated board, packaging cartons, etc., and has become one of the adhesive varieties with the most development potential. However, traditional starch-based adhesives have the following problems: 1) After the carrier starch used to prepare cooked pulp is completely hydrolyzed, it mainly helps the main starch in the raw pulp to disperse stably. The greater the proportion of carrier starch, the worse the adhesion of the starch adhesive. The reduction of the proportion of carrier starch will cause the starch adhesive to stratify and the bonding performance to be unstable; 2) The sodium hydroxide or other chemical modification agents contained in the cooked pulp will continue to act on the hydrolyzed starch in the cooked pulp and the main starch in the raw pulp, causing the starch adhesive to undergo irreversible hydrolysis, association, cross-linking and other complex reactions during its stay in the storage tank. At the same time, after the glue is gelatinized and formed, the sodium hydroxide or other chemical modification agents will also have uncontrollable side reactions with materials such as cellulose in the paperboard, thereby reducing the bonding effect to varying degrees. 3) After starch adhesive is gelatinized and formed, it is easy to absorb water and swell in a high humidity environment, causing serious quality problems such as degumming. Although some studies have used chemical modifications such as oxidation and cross-linking of the main starch in the raw pulp to inhibit the absorption of water by starch hydroxyl groups after gelatinization and forming, the overall moisture-proof effect is still not ideal.

[0003] In order to solve the problems of low strength, poor toughness, and poor high temperature resistance of starch adhesives, Chinese invention patent CN116676058B discloses a high-strength and high-toughness starch adhesive and a preparation process. After the starch adhesive is compounded with a water-based polyurethane containing a POSS three-dimensional cross-linked structure, a stable interpenetrating network structure is formed, which inhibits water molecules from entering the adhesive, and overcomes the problem of starch adhesives bubbling and debonding when they come into contact with water, thereby improving the water resistance and waterproofness of the adhesive, and maintaining a long water resistance time at a high temperature of 80°C, with excellent high temperature resistance and water resistance and waterproofing properties. However, since organic chemical reagents such as polytetramethylene glycol are used in this patent, the environmental protection needs to be further improved, and the production cost of this patent is relatively high.

[0004] In order to solve the problems of poor fluidity, poor film-forming properties, and low bonding strength of traditional starch-based adhesives, PCT patent application WO2021036197A1 discloses a method for preparing starch-based adhesives, using oxidized corn starch as a matrix and polyvinyl alcohol / glycerol as a compound plasticizer. The starch-based viscose is obtained by adding borax and alkali solution to the oxidized corn starch emulsion and then heating it. Due to the addition of borax, alkali solution, and strong oxidant sodium hypochlorite, the starch adhesive will undergo irreversible hydrolysis, association, cross-linking and other complex reactions during its stay in the storage tank. At the same time, after the glue is gelatinized and formed, the borax and alkali solution will also have uncontrollable side reactions with materials such as cellulose in the cardboard, reducing the bonding effect.

[0005] Regarding the problem that starch adhesives are prone to absorbing water and swelling in a high-humidity environment after being gelatinized and formed, Chinese invention patent application CN108342172A proposes a method for preparing moisture-proof starch glue, wherein soybeans are used as raw materials to obtain an alkalized liquid, the alkalized liquid is placed in a centrifuge for centrifugal separation to obtain an upper clear liquid, the upper clear liquid is acidified with dilute hydrochloric acid to obtain a lower protein precipitate, half of the protein precipitate is added to a sodium hydroxide solution to obtain a heat-alkali degraded protein liquid, the other half of the protein precipitate is treated to obtain an acid-heat-treated soybean protein powder, the heat-alkali degraded protein liquid and the acid-heat-treated soybean protein powder are mixed and heated with a starch-grafted styrene-acrylic latex to obtain a moisture-proof starch glue, and by grafting styrene-acrylic latex on starch, the water absorption effect of the hydroxyl group on the starch can be shielded, thereby improving the moisture-proof performance of the starch glue, and the soybean protein undergoes alkali modification at a higher sodium hydroxide solution concentration, and part of the soybean protein undergoes hydrolysis, resulting in a decrease in the surface tension of the adhesive emulsion and an increase in the contact angle, thereby achieving a moisture-proof effect, and having broad application prospects. However, the above preparation process is complicated, a strong base is used in the reaction process, and its moisture-proof effect needs to be further improved.

[0006] Pickering emulsion refers to a new type of emulsion that uses solid particles adsorbed at the oil-water interface instead of surfactants as stabilizers. Its preparation process is simple and the emulsion has excellent stability. For example, Chinese invention patent CN110506930B discloses a starch-based high-stability Pickering emulsion and its preparation method. First, the starch raw material is prepared into a starch slurry with a dry basis mass fraction of 5-20%, gelatinized in a boiling water bath and cooled, and then centrifuged and graded after excessive ethanol is added. After precipitation and drying, V-shaped crystalline starch is obtained; the molten fatty acid and V-shaped crystalline starch are fully mixed and continuously stirred, and starch-lipid composite particles are obtained after blast drying; the starch-lipid composite particles are prepared into a suspended aqueous solution, and the suspended aqueous solution is mixed with liquid oil and high-speed shearing to obtain a starch-based high-stability Pickering emulsion, the emulsification index of which can reach 100%, the droplets are evenly distributed, the average particle size is 10.13-25.20μm, and there is no stratification after storage for three months. However, the patent does not involve the relevant content of adhesives.

[0007] Therefore, there is an urgent need to develop starch adhesives that have high effective starch content, no sodium hydroxide or other oxidant residues, and are effectively moisture-proof after gluing. Summary of the invention

[0008] In view of the problems existing in the prior art, the present invention provides a starch-based adhesive and a preparation method and application thereof. Without using chemical modification means, it is first proposed to use a starch adhesive that synergistically constructs a stable Pickering emulsion system with water-soluble colloids, natural starch and liquid oil. The starch adhesive has the characteristics of high effective starch content, no residual chemical reagents such as sodium hydroxide, and effective moisture-proof after gluing. It essentially solves the main defects of the prior art and promotes the technological progress of corrugated paper packaging materials.

[0009] The first aspect of the present invention is to provide a starch-based adhesive, comprising the following components: 100 parts of water, 0.1-1 parts of water-soluble colloid, 25-35 parts of natural starch, and 2-5 parts of liquid oil.

[0010] Preferably, the water-soluble colloid is selected from at least one of gelatin, carrageenan, pectin, locust bean gum, acetate starch and chitosan.

[0011] Preferably, the natural starch is selected from at least one of corn starch, waxy corn starch, high amylose corn starch, grain amaranth starch, tapioca starch, quinoa starch, potato starch, wheat starch, barley starch, rice starch, sorghum starch, sweet potato starch, sweet potato starch and bean starch.

[0012] Preferably, the liquid oil is selected from at least one of mineral oil, corn oil, soybean oil, peanut oil, caprylic / decanoic acid glyceride (ODO), sunflower oil, olive oil, camellia oil and blended oil.

[0013] Preferably, the mass ratio of the water-soluble colloid, natural starch and liquid oil is 0.3-0.8:25-30:3-5.

[0014] The second aspect of the present invention is to provide a method for preparing the above-mentioned starch-based adhesive, comprising the following steps:

[0015] S1. Add water-soluble colloid into water, and after fully dissolving, adjust the pH value to 5-7 to obtain a colloid solution;

[0016] S2, adding natural starch to the colloidal solution obtained in step S1, shearing and emulsifying, to form a starch dispersion;

[0017] S3, adding liquid oil to the starch dispersion obtained in step S2, shearing and emulsifying, to obtain a Pickering emulsion, which is a starch adhesive that can be used industrially.

[0018] Preferably, the shear emulsification temperature in step S2 and step S3 is independently selected from 20-40°C.

[0019] Preferably, the rotation speeds of the shear emulsification in step S2 and step S3 are independently selected from 2000-10000 rpm.

[0020] Preferably, the time of shear emulsification in step S2 and step S3 is independently selected from 3-30 min.

[0021] The third aspect of the present invention relates to the use of the above-mentioned starch-based adhesive or the starch-based adhesive prepared according to the above-mentioned preparation method in the preparation of corrugated paper packaging materials.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1) All starches in the present invention are ungelatinized granular starches, that is, all are effective starches that can produce adhesive properties after being glued, and the proportion of effective starch is significantly increased, thereby improving the adhesive properties;

[0024] 2) The Pickering emulsion system formed by water-soluble colloid, natural starch and liquid oil helps the starch adhesive to become a uniform and stable dispersion system within a certain period, which is conducive to stable industrial production;

[0025] 3) No sodium hydroxide is used for hydrolysis, and no other chemical modification reagents are used. The starch adhesive formula is simple, the starch molecular structure is stable, and the performance stability and safety and environmental protection of the adhesive are significantly improved;

[0026] 4) Liquid oil can not only help starch particles to be stably suspended and dispersed in the dispersion system, but also work together with gelatinized starch molecules after gelatinization, and through complex spatial molecular effects, it is irreversibly transformed into a hydrophobic gel system, thus having an excellent moisture-proof effect. DETAILED DESCRIPTION

[0027] The following non-limiting examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way. The following content is merely an exemplary description of the scope of the present invention, and those skilled in the art can make various changes and modifications to the present invention based on the disclosed content, which should also fall within the scope of the present invention.

[0028] Embodiment 1:

[0029] A starch-based adhesive comprises the following components: 100 g of water, 0.5 g of chitosan, 27.5 g of corn starch and 4.6 g of soybean oil.

[0030] The preparation method is:

[0031] S1: Add 0.5 g of chitosan to 100 g of water, fully dissolve it under pH = 3, and then adjust the pH value to 6 to obtain a colloidal solution;

[0032] S2: adding 27.5 g corn starch to the colloidal solution obtained in step 1, and emulsifying the mixture at 30° C. and 5000 rpm for 3 min to form a starch dispersion;

[0033] S3: 4.6 g soybean oil was further added to the starch dispersion obtained in step 2, and the mixture was sheared and emulsified at 8000 rpm for 5 min at 30° C. to form a starch adhesive of a stable Pickering emulsion system.

[0034] Embodiment 2:

[0035] A starch-based adhesive comprises the following components: 100g water, 1g acetate starch, 35g waxy corn starch and 5g blending oil.

[0036] The preparation method is:

[0037] S1: Add 1 g of acetate starch to 100 g of water, and after fully dissolving, adjust the pH value to 7 to obtain a colloidal solution;

[0038] S2: adding 35 g of waxy corn starch to the colloidal solution obtained in step 1, and emulsifying the mixture at 30° C. and 10,000 rpm for 3 min to form a starch dispersion;

[0039] S3: 5 g of blending oil was further added to the starch dispersion obtained in step 2, and shear emulsified at 5000 rpm for 10 min at 20° C. to form a starch adhesive of a stable Pickering emulsion system.

[0040] Embodiment 3:

[0041] A starch-based adhesive comprises the following components: 100 g of water, 0.1 g of gelatin, 25 g of tapioca starch and 2 g of caprylic / capric glyceride.

[0042] The preparation method is:

[0043] S1: Add 0.1 g of gelatin to 100 g of water, and after it is fully dissolved, adjust the pH value to 5 to obtain a colloidal solution;

[0044] S2: adding 25 g of cassava starch to the colloidal solution obtained in step 1, and emulsifying the mixture at 40° C. and 5000 rpm for 3 min to form a starch dispersion;

[0045] S3: 2 g of caprylic acid glyceride was further added to the starch dispersion obtained in step 2, and the mixture was sheared and emulsified at 7500 rpm for 5 min at 30° C. to form a starch adhesive of a stable Pickering emulsion system.

[0046] Comparative Example 1:

[0047] The two-step starch adhesive formulation disclosed in the reference was prepared.

[0048] S1. Add 1.5g corn starch to 6.3g water, stir evenly, then add 0.28g sodium hydroxide, stir for 15min to make a cooked slurry;

[0049] S2. Add 26 g corn starch to 93.7 g water, stir evenly to form raw slurry, then add the cooked slurry obtained in step 1, stir for 10 minutes, and form a conventional starch adhesive.

[0050] Comparative Example 2:

[0051] A starch-based adhesive comprises the following components: 100 g of water, 0.05 g of chitosan, 27.5 g of corn starch and 4.6 g of soybean oil.

[0052] The preparation method is:

[0053] S1: Add 0.05 g of chitosan to 100 g of water, fully dissolve it under pH = 3, and then adjust the pH value to 6 to obtain a colloidal solution;

[0054] S2: adding 27.5 g corn starch to the colloidal solution obtained in step 1, and emulsifying the mixture at 30° C. and 5000 rpm for 3 min to form a starch dispersion;

[0055] S3: 4.6 g soybean oil was further added to the starch dispersion obtained in step 2, and shear emulsification was performed at 8000 rpm for 5 min at 30° C. to obtain the starch dispersion.

[0056] The formed starch adhesive is basically stable within 10 minutes and then delaminated, so it is not suitable for use as an industrial starch adhesive.

[0057] Comparative Example 3:

[0058] A starch-based adhesive comprises the following components: 100 g of water, 0.5 g of chitosan, 27.5 g of corn starch and 6 g of soybean oil.

[0059] The preparation method is:

[0060] S1: Add 0.5 g of chitosan to 100 g of water, fully dissolve it under pH = 3, and then adjust the pH value to 6 to obtain a colloidal solution;

[0061] S2: adding 27.5 g corn starch to the colloidal solution obtained in step 1, and emulsifying the mixture at 30° C. and 5000 rpm for 3 min to form a starch dispersion;

[0062] S3: 6 g of soybean oil was further added to the starch dispersion obtained in step 2, and the mixture was sheared and emulsified at 8000 rpm for 5 min at 30° C. to obtain the starch dispersion.

[0063] The formed starch adhesive is basically stable within 10 minutes, but has obvious floating oil and then separates into layers, so it is not suitable for use as an industrial starch adhesive.

[0064] Comparative Example 4:

[0065] A starch-based adhesive comprises the following components: 100 g of water, 0.5 g of chitosan, 27.5 g of corn starch and 1 g of soybean oil.

[0066] The preparation method is:

[0067] S1: Add 0.5 g of chitosan to 100 g of water, fully dissolve it under pH = 3, and then adjust the pH value to 6 to obtain a colloidal solution;

[0068] S2: adding 27.5 g corn starch to the colloidal solution obtained in step 1, and emulsifying the mixture at 30° C. and 5000 rpm for 3 min to form a starch dispersion;

[0069] S3: 1 g of soybean oil is further added to the starch dispersion obtained in step 2, and the mixture is sheared and emulsified at 8000 rpm for 5 min at 30° C. to obtain the starch dispersion.

[0070] The formed starch adhesive is basically stable within 30 minutes and then delaminated, so it is not suitable for use as an industrial starch adhesive.

[0071] Comparative Examples 2-4 illustrate that the starch adhesive of the present application is a metastable system constructed by water-soluble colloid, natural starch and liquid oil. Too little water-soluble colloid addition, too much or too little liquid oil addition will cause the starch adhesive system to become unstable and cannot be used industrially. Due to the high price of water-soluble colloids, excessive addition will lead to increased production costs, and at the same time, the viscosity of the system will increase, making it difficult to transport by pipeline. Starch adhesives with too little liquid oil addition, even if prepared and used immediately, will result in unclear gelation with starch molecules after gelatinization, and the water absorption rate will not decrease significantly.

[0072] Test Example 1:

[0073] Item 1: The initial viscosity and viscosity after 24 hours of the starch adhesives of the above-mentioned Examples 1-3 and Comparative Example 1 were directly measured by a rotor viscometer; the initial pH value and pH value after 24 hours of the starch adhesives of the above-mentioned Examples 1-3 and Comparative Example 1 were measured; the starch adhesives of the above-mentioned Examples 1-3 and Comparative Example 1 were gelatinized in a boiling water bath for 30 minutes, kept at 80°C for 10 minutes, and then the initial viscosity and viscosity after 24 hours were measured by a rotor viscometer; the bonding strength of the starch adhesive applied to corrugated cardboard was measured according to the GBT6548 method; the water absorption rate of the sample after gelatinization and drying was measured, and the completely dried sample after gelatinization was placed at a temperature of 37°C and a humidity of 75% for 2 hours, and the mass of the sample before and after placement was weighed, and the water absorption rate was calculated according to the following formula:

[0074] Water absorption (%) = (m1-m0) / m0×100%;

[0075] Where m0 is the initial mass of the sample, and m1 is the mass of the sample after being placed for 2 hours.

[0076] The test results are shown in Table 1.

[0077] Table 1: Performance test results of adhesives of Examples 1-3 of the present invention and Comparative Example 1

[0078]

[0079] According to the data in the table, it can be seen that the viscosity of the adhesive of the present application remains basically unchanged after being placed for 24 hours. Therefore, the adhesive obtained by the present invention becomes a uniform, stable and mild dispersion system within a certain period, which is conducive to stable industrial production. However, as time goes by, the viscosity of Comparative Example 1 increases significantly, and the starch undergoes irreversible hydrolysis, resulting in a continuous decrease in the effective starch content, and the actual bonding performance after gelatinization continues to decrease; the viscosity of the adhesives obtained in Examples 1-3 of the present invention after gelatinization and the bonding strength applied to corrugated cardboard are significantly higher than those in Comparative Example 1. Since all the starches in the present invention are ungelatinized granular starch, that is, all are effective starches that can produce bonding after gluing, the proportion of effective starch is significantly increased, thereby improving the bonding performance, and the system still maintains a constant viscosity for 24 hours after gelatinization, while Comparative Example 1 still has an irreversible hydrolysis and viscosity reduction phenomenon after gelatinization; in terms of water absorption, it can be seen that the water absorption rates of the adhesives obtained in Examples 1-3 of the present invention are significantly lower than those in Comparative Example 1.

[0080] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.

Claims

1. A starch-based adhesive comprising the following components: 100 parts of water, 0.1-1 parts of water-soluble colloid, 25-35 parts of natural starch, and 2-5 parts of liquid grease.

2. The starch-based adhesive according to claim 1, characterized in that: The water-soluble colloid is selected from at least one of gelatin, carrageenan, pectin, locust bean gum, acetate starch and chitosan.

3. The starch-based adhesive according to claim 1, characterized in that: The natural starch is selected from at least one of corn starch, waxy corn starch, high amylose corn starch, grain amaranth starch, tapioca starch, quinoa starch, potato starch, wheat starch, barley starch, rice starch, sorghum starch, sweet potato starch, sweet potato starch and bean starch.

4. The starch-based adhesive according to claim 1, characterized in that: The liquid oil is selected from at least one of mineral oil, corn oil, soybean oil, peanut oil, caprylic / capric glyceride, sunflower oil, olive oil, camellia oil and blended oil.

5. The starch-based adhesive according to claim 1, characterized in that: The mass ratio of the water-soluble colloid, the natural starch and the liquid oil is 0.3-0.8:25-30:3-5.

6. A method for preparing the starch-based adhesive according to any one of claims 1 to 5, comprising the following steps: S1. Add water-soluble colloid into water, and after fully dissolving, adjust the pH value to 5-7 to obtain a colloid solution; S2, adding natural starch to the colloidal solution obtained in step S1, shearing and emulsifying, to form a starch dispersion; S3, adding liquid oil to the starch dispersion obtained in step S2, shearing and emulsifying, to obtain a Pickering emulsion, which is a starch adhesive that can be used industrially.

7. The preparation method according to claim 6, characterized in that: The shear emulsification temperature in step S2 and step S3 is independently selected from 20-40°C.

8. The preparation method according to claim 6, characterized in that: The rotation speed of the shear emulsification in step S2 and step S3 is independently selected from 2000-10000 rpm.

9. The preparation method according to claim 6, characterized in that: The time of shear emulsification in step S2 and step S3 is independently selected from 3-30 min.

10. Use of the starch-based adhesive according to any one of claims 1 to 5 or the starch-based adhesive prepared according to the preparation method according to any one of claims 6 to 9 in preparing corrugated paper packaging materials.

Citation Information

Patent Citations

  • Preparation method of moistureproof starch glue

    CN108342172A

  • A starch-based highly stable Pickering emulsion and its preparation method

    CN110506930B

  • A high-strength, high-toughness starch adhesive and its preparation process

    CN116676058B

  • Preparation method for starch-based adhesive

    WO2021036197A1